2020
DOI: 10.1016/j.envint.2019.105188
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 on the London Underground

Abstract: HighlightsPM2.5 concentrations on the London Underground are higher than ambient and other subway systems.Dust is generated by the wear of train components and resuspended by passing trains.Variability is caused by ventilation rates and is highest in long underground sections.The differing chemical composition of PM2.5 necessitates calibration of portable instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 70 publications
6
42
1
Order By: Relevance
“…London are up to 26 times more polluted than the ambient background locations and the roadside environment (that have median PM2.5 level of 14 μg m −3 [26]). Moreover, the average NO2 concentrations within the LU network was reported to be 51 μg m −3 [27]; which is 27.5% higher than the NO2 limit values for the protection of human health [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…London are up to 26 times more polluted than the ambient background locations and the roadside environment (that have median PM2.5 level of 14 μg m −3 [26]). Moreover, the average NO2 concentrations within the LU network was reported to be 51 μg m −3 [27]; which is 27.5% higher than the NO2 limit values for the protection of human health [28].…”
Section: Resultsmentioning
confidence: 99%
“…As per TfL's guidance to LU users [25], 40 LU stations across its network were closed as part of the UK Government's response to COVID-19. The median PM2.5 levels recorded by [26] for 27 of these 40 closed stations range from 0-50 μg m −3 (5 stations), 50-100 μg m −3 (9 stations), 100-200 5 μg m −3 (5 stations), 200-300 μg m −3 (6 stations) and greater than 300 μg m −3 (2 stations) (see Table S1). Of the 230 operating stations, the median PM2.5 levels recorded for 219 stations range from 0-50 μg m −3 (56 stations), 50-100 μg m −3 (15 stations), 100-200 μg m −3 (15 stations), 200-300 μg m −3 (18 stations) and greater than 300 μg m −3 (7 stations) [26] (see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The main sources of metal emissions to air in the UK include metal smelting and refining processes, as well as transport and domestic biomass burning [ 8 ], and the most abundant metal is iron, with concentrations typically representing up to 1% of the aerosol mass and fluctuating between 400 and 600 ng/m 3 in the last two decades [ 8 ]. Higher concentrations have been reported in some locations, including the London Underground where iron has been found to comprise greater than 40% by mass of PM 2.5 [ 9 , 10 , 11 , 12 ]. Iron is also the dominant metal in the ultrafine fraction in the UK [ 13 ] and other countries, including urban settings in China [ 14 ] and Mexico [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the London Underground, Seaton et al [41] reported higher platform concentrations of 480 µg/m 3 . Recently, Smith et al [42] assessed day to day variation in LU concentrations and compared them with those above ground. During their campaign, 22 repeat journeys were made on weekday mornings over a period of five months.…”
Section: Pm 25 Concentration In the London Undergroundmentioning
confidence: 99%